Before He Needs (A Mackenzie White Mystery-Book 5) - Blake, Pierce (Lukeman Literary, 2017)
From Blake Pierce, bestselling author of ONCE GONE (a #1 bestseller with over 900 five star reviews), comes book #5 in the heart-pounding Mackenzie White mystery series. In BEFORE HE NEEDS (A Mackenzie White Mystery-Book 5), FBI special agent Mackenzie White finds herself summoned to crack a case she has never encountered before: the victim is not a man or a woman-but a couple. The third couple found dead in their homes this month. As Mackenzie and the FBI scramble to figure out who would want happily-married couples dead, her search takes her deep into a disturbing world and subculture. She quickly learns that all is not what it seems behind the picket fences of perfectly-suburban homes-and that darkness lurks at the edge of even the happiest-seeming families. As her hunt morphs into a deadly game of cat-and-mouse, Mackenzie, still struggling to find her own father's killer, realizes she may be in too deep-and that the killer she seeks may be the most elusive of all: shockingly normal. A dark psychological thriller with heart-pounding suspense, BEFORE HE NEEDS is book #5 in a riveting new series-with a beloved new character-that will leave you turning pages late into the night. Book #6 in the Mackenzie White Mystery series will be available soon.
Keywords: Krimi, detektivky